Discriminating between the origins of remotely sensed circular structures: carbonate mounds, diapirs or periclinal folds? Purbeck Limestone Group, Weymouth Bay, UK - Bosence,DWJ; Collier,JS; Fleckner,S; Gallois,A; Watkinson,IM (Journal of the Geological Society, 2018)
Many sedimentary rock successions contain plan-view circular structures, such as impacts, diapirs and carbonate build-ups. When remotely sensed, it can be difficult to discriminate between their formation mechanisms. Here we examine this problem by assessing the origins of circular structures imaged in high-resolution multibeam bathymetric data from Weymouth Bay, UK. The imagery shows 30–150m across, concave-down structures within the upper Purbeck Limestone Group on the southern limb of the Purbeck Anticline. Similar structures have not been identified in the extensive outcrops around the bay. The morphology and geological setting of the structures are consistent with three different interpretations: carbonate mounds, periclinal folds and evaporite diapirs. However, none of these structures has been previously recorded in the upper Purbeck Limestone Group outcrops of this internationally renowned geological region. We apply a scoring system to 25 features of the circular structures to discriminate between these three alternative interpretations. This analysis indicates that evaporite diapirs are the least likely and carbonate mounds the most likely origin of the structures. The presence of carbonate mounds revises the upper Purbeck palaeofacies distribution in its type area and provides an analogue for the exploration for hydrocarbon reservoirs in lacustrine mounds.